Measurement Model of Soft Skills: Work Environment as a Mediator of Teaching Success - Maren , Macqual Stephen; Salleh, Umi Kalsum Mohd; Zulnaid, Hutkemri (International Journal of Psychosocial Rehabilitation, 2020)
Analysing the level of soft skills acquired by would-be teachers and its effect on their teaching performance reveals that value must be created before it is demonstrated. This work aims to establish the validity and reliability of an instrument designed for data collection for the main study. A non-experimental research design was adopted. Three instruments comprising 60 items were used to collect data from 95 final-year students of the faculties of education of federal universities in north–central Nigeria. No significant relationship was hypothesised between the measurement model and the hypothesised structural model, that is, the recycled questions were not accurate measures of their respective constructs. Partial least square structural equation modelling was performed by using SmartPLS version 3.0. The indicator loadings ranged between 0.6 and 0.9, the indicator reliability was ≥4.0 and the VIF was >0.5 at a 5% level of significance. Filtering the indicators into their respective constructs revealed that their Cronbach’s alpha and composite reliability values range between 0.8 and 0.9, whereas their average variances extracted range from 0.5 to 0.8. Such high validity and reliability indicate that the recycled questions are accurate measures of their respective constructs, thereby suggesting that these questions can be used to collect high-quality data for the main study.